ANALISIS DAN SIMULASI KINERJA (DAYA DAN EFISIENSI) PADA SUDU TURBIN ANGIN SAVONIUS VERTIKAL TIPE U DENGAN SOFTWARE - sidiq, akhmad; Subagyo, Tulus (POLITALA PRESS, 2023)
Increased energy needs and environmental concerns have encouraged exploration of renewable energy sources. The research was to analyze savonius' performance and design of wind turbines as an alternative to electricity generation. Wind velocity measurement in turbines is used in anemometers, as well as in their effects on energy generation potential. In design, the study analyzes the level u wind turbine framework of dimension, geometry, voltage distribution, and material resistance. A structural and safety factor calculation is done to ensure that the turbine frame can support an anticipated load without failure. In this study computes the power extracted from the wind through the turbine. From this study produce 26.6 joules of kinetic energy and a 9.60 watt output output at an efficient rate of 5.28%.